Drivers, trends, and consequences of changing household employment patterns in rural Bangladesh - Sen, Binayak; Dorosh, Paul A.; Ahmed, Mansur; van Asselt, Joanna (International Food Policy Research Institute, 2018)
This paper focuses on rural nonfarm development via the route of salaried employment. The analysis is at the rural household level for two types of households: “mixed” households whereby some workers remain in the farm sector and others pursue nonfarm activities and the rural households who are exclusively dependent on nonfarm employment (rural nonfarm). The study has produced three major findings. First, compared with the mixed or farm-only households, nonfarm households seem to have more income. Second, nonfarm households discourage unpaid work, especially among female workers, in sharp contrast to the increasing share of unpaid work in both farm and mixed households. Third, nonfarm households increasingly rely, for their livelihoods, on salaried employment, which is likely to be of a more durable nature than the juggling of multiple occupations observed in the case of mixed households. Analysis of possible factors influencing the formation of nonfarm households shows the importance of human capital, non-land assets, and proximity to larger towns, while natural shocks seem to encourage the formation of mixed households and remittance from abroad tends to stimulate the farm orientation.